Ocular complications of boxing. Issue 2 (21st January 2005) - Bianco, M; Vaiano, A S; Colella, F; Coccimiglio, F; Moscetti, M; Palmieri, V; Focosi, F; Zeppilli, P
Abstract : Objectives: To investigate the prevalence of ocular injuries in a large population of boxers over a period of 16 years, in particular, the most severe lesions that may be vision threatening. Methods: Clinical records of the medical archive of the Italian Boxing Federation were analysed. A total of 1032 boxers were examined from February 1982 to October 1998. A complete ophthalmological history was available for 956, who formed the study population (a total of 10 697 examinations). The following data were collected: age when started boxing; duration of competitive boxing career (from the date of the first bout); weight category; a thorough ocular history. The following investigations were carried out: measurement of visual acuity and visual fields, anterior segment inspection, applanation tonometry, gonioscopy, and examination of ocular fundus. Eighty age matched healthy subjects, who had never boxed, formed the control group. Results: Of the 956 boxers examined, 428 were amateur (44.8%) and 528 professional (55.2%). The median age at first examination was 23.1 (4.3) years (range 15–36). The prevalence of conjunctival, corneal, lenticular, vitreal, ocular papilla, and retinal alterations in the study population was 40.9% compared with 3.1% in the control group (p⩽0.0001). The prevalence of serious ocular findings (angle, lens, macula, and peripheral retina alterations) was 5.6% in boxers and 3.1% in controls (NS). Conclusions: Boxing does not result in a higher prevalence of severe ocular lesions than in the general population. However, the prevalence of milder lesions (in particular with regard to the conjunctiva and cornea) is noteworthy, justifying the need for adequate ophthalmological surveillance.